Performance of Highway Embankments Constructed Over Sri Lankan Peaty Soils - Karunawardena, Asiri; Toki, Masakazu (International Journal of Integrated Engineering, 2014)
The construction of the Southern Expressway in Sri Lanka involved extensive ground improvement work as many parts of the Expressway traverses through flood plains and marshy ground consisting of very soft peat, organic soils, and clays. Depending on the ground conditions, various ground improvement methods including remove and replacement, preloading, preloading with vertical drains, dynamic compaction and vacuum consolidation were applied to improve the soft soil to build the embankments with heights varying from 2m to 12m. In this project, embankments of about 4 km in length were constructed by improving the peaty soil basically by the application of the heavy tamping method.  The length of the embankments that were built by improving the peaty soil by vacuum assisted surcharging is around 2.5 km. The details of the field instrumentation program and field monitoring program to assess the soft ground improvement are presented. The performance of the ground improvement was evaluated in terms of the degree of consolidation, improvement of the physical and engineering properties, increase in preconsolidation pressure and gain in shear strength of the peaty soil. The results of the post construction surface settlement monitoring of the expressway carried out up to date reconfirm that the ground improvement work was very successful and the expected residual settlements are well below the allowable limit of the contract.